2022
DOI: 10.3390/bioengineering9090441
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Transcutaneous Spinal DC Stimulation as a Neurorehabilitation ALS Therapy in Awake G93A Mice: The First Step to Clinical Translation

Abstract: Spinal direct current stimulation (sDCS) modulates motoneuron (MN) excitability beyond the stimulation period, making it a potential neurorehabilitation therapy for amyotrophic lateral sclerosis (ALS), a MN degenerative disease in which MN excitability dysfunction plays a critical and complex role. Recent evidence confirms induced changes in MN excitability via measured MN electrophysiological properties in the SOD1 ALS mouse during and following invasive subcutaneous sDCS (ssDCS). The first aim of our pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Indeed, according to the earliest reports [ 14 , 15 , 16 ], all the results in animal studies confirmed that both anodal and cathodal tsDCS induce local and cortical plastic changes [ 38 , 39 , 40 , 41 , 42 , 43 ] in rat motoneurons, which considerably outlast the time of polarization [ 38 , 39 , 40 , 41 , 42 ]. Most studies found a depolarization and, thus, an increase of motor responses following cathodal tsDCS, and a hyperpolarization and, thus, a decrease of motor responses following anodal tsDCS [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In the authors’ hypothesis, cathodal tsDCS increases evoked synaptic transmission, and, by depolarizing cell bodies, it augments motoneuron activity through induction of calcium release [ 14 , 15 , 16 , 38 ], while anodal tsDCS exerts opposite effects [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Indeed, according to the earliest reports [ 14 , 15 , 16 ], all the results in animal studies confirmed that both anodal and cathodal tsDCS induce local and cortical plastic changes [ 38 , 39 , 40 , 41 , 42 , 43 ] in rat motoneurons, which considerably outlast the time of polarization [ 38 , 39 , 40 , 41 , 42 ]. Most studies found a depolarization and, thus, an increase of motor responses following cathodal tsDCS, and a hyperpolarization and, thus, a decrease of motor responses following anodal tsDCS [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In the authors’ hypothesis, cathodal tsDCS increases evoked synaptic transmission, and, by depolarizing cell bodies, it augments motoneuron activity through induction of calcium release [ 14 , 15 , 16 , 38 ], while anodal tsDCS exerts opposite effects [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, according to the earliest reports [14][15][16], all the results in animal studies confirmed that both anodal and cathodal tsDCS induce local and cortical plastic changes [38][39][40][41][42][43] in rat motoneurons, which considerably outlast the time of polarization [38][39][40][41][42]. Most studies found a depolarization and, thus, an increase of motor responses following cathodal tsDCS, and a hyperpolarization and, thus, a decrease of motor responses following anodal tsDCS [38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations